2010
DOI: 10.1590/s0103-90162010000200013
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pH and temperature on peroxidase and polyphenoloxidase activities of litchi pericarp

Abstract: After harvesting litchi, the red color of the fruit pericarp is rapidly lost resulting in discoloration and browning during storage and marketing. The loss of the red color is caused by the degradation or loss of stability of anthocyanins. The action of peroxidase and polyphenoloxidase is usually related to the browning and discoloration of fruits of various species. This study aimed to evaluate the influence of pH and temperature on peroxidase and polyphenoloxidase activities, in a partially purified preparat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(55 citation statements)
references
References 16 publications
4
38
0
7
Order By: Relevance
“…The reaction was initiated by adding 0.8M H 2 0 2 and the breakdown of the H 2 O 2 was monitored for 3 minutes at a 30 second interval, at 24 ºC, by recording absorbances at 470 nm in a spectrophotometer (Biowaveii+, Cambridge, England). The activity of the enzyme was calculated and expressed as a change in absorbance min -1 mg -1 (Mizobutsi et al, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…The reaction was initiated by adding 0.8M H 2 0 2 and the breakdown of the H 2 O 2 was monitored for 3 minutes at a 30 second interval, at 24 ºC, by recording absorbances at 470 nm in a spectrophotometer (Biowaveii+, Cambridge, England). The activity of the enzyme was calculated and expressed as a change in absorbance min -1 mg -1 (Mizobutsi et al, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, mix II color changed on the surface to a light brown color after 3 days of fermentation. This color change might be due to enzymatic browning promoted by polyphenol oxidase (PPO), which causes the oxidation of phenolic compounds in the food materials and remains active at pH values of 4.0 to 8.0 (depending on plant sources and temperature) (Mizobutsi et al, 2010). Hunaefi et al (2013) reported that red cabbage contained high level of phenolic compounds, and that the fermentation caused a slight increase in phenolic compounds in red cabbage.…”
Section: Color Valuementioning
confidence: 99%
“…The reaction was initiated by adding 0.8M H 2 O 2 and the breakdown of the H 2 O 2 was monitored for 2.5 minutes at a 30 second interval, at 24 ºC, by recording absorbances at 470 nm in a spectrophotometer (Biowaveii+, Cambridge, England). The activity of the enzyme was calculated and expressed as absorbance units/min/mg (Mizobutsi et al, 2010).…”
Section: Issn: 2320-5407mentioning
confidence: 99%